Las abejas atarrá de la región mesoamericana del género y subgénero Trigona (Apidae-Meliponini) - Wille, Alvaro (1965)
This paper deals with the stingless be es of the genus and subgenus Trigona of Middle America (Mexico to Panama). Information is presented about the following: a) Aspects of biology such as swanning and founding of new colonie;, pollination, communication, flight range, and defense. b) Types of nests: aercal or exposed, riests made inside of aercal nests of Nasutitermis nests inside of tree holes, and subterranean nests. c) The economic importance of these bees as pollinators, as destructive insects of several species of fruit trees, as possible vectors of the Moko disease in bananas. d) A key for the identification of the 8 species of Middle America is provided. e) General discussion of each species, including generalities diagnostic characters, nests, and distribution.